The relationship between teachers' language experience and their inclusion of pupils' home languages in school life. (2nd January 2020) - Gilham, Polly; Fürstenau, Sara
Abstract: In this article, we present a qualitative investigation which was conducted as part of a project on school development in the field of multilingualism in Germany. In order to gain insight into the relationship between primary school teachers' language experience and their practice regarding the inclusion of pupils' home languages at school, ethnographic fieldwork was undertaken in three professional development sessions. In the three individual case studies chosen for analysis in this paper, we found clear indications of links between the participants' experiences with language, their language attitudes and their depictions of their pedagogical practice regarding migration-related multilingualism. The prevalence of different languages in the participants' everyday lives seemed to be closely linked to their willingness to include their pupils' home languages in their teaching. However, it would be overly simplistic to conclude that multilingual staff are better able than their monolingual peers to adapt their practice in this way. We observed that, above all, the participants' emotional associations with language and the meaning they attached to their experiences appeared to influence their perceptions of their ability to incorporate different languages into school life.